2016
DOI: 10.1155/2016/8480963
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Natamycin in Turkish Yoghurt

Abstract: This study was aimed at developing RP-HPLC method for determination of natamycin in Turkish yoghurt. Chromatographic separation was achieved on a C8 column (150 mm × 4.6 mm × 5 µm) with a mobile phase of methanol : water : acetic acid (12 : 8 : 1 v/v/v), at 1 mL/min flow rate with a detection of 303 nm. Natamycin was spiked into handmade yoghurt samples and used for validation. The method has been fully validated according to ISO 9233-2, 2007 (IDF 140-2, 2007). It was successfully applied to determination of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Sorbic acid is a polyunsaturated fatty acid (PUFA); thus, its metabolism in humans as well as other acids generally shows less toxic effect than benzoic acid [1]. Natamycin (C 33 H 47 NO 13 ) also known as pimaricin is a polyene macrolide with antifungal effects which was generated by aerobic fermentation of Streptomyces natalensis and related species [11,19,21], but inactive against bacteria [22]. It is a white, odorless, and tasteless powder [21] which is considered to be safe in food industry due to its sensitivity to ultraviolet light and acidic pH [22].…”
Section: Resultsmentioning
confidence: 99%
“…Sorbic acid is a polyunsaturated fatty acid (PUFA); thus, its metabolism in humans as well as other acids generally shows less toxic effect than benzoic acid [1]. Natamycin (C 33 H 47 NO 13 ) also known as pimaricin is a polyene macrolide with antifungal effects which was generated by aerobic fermentation of Streptomyces natalensis and related species [11,19,21], but inactive against bacteria [22]. It is a white, odorless, and tasteless powder [21] which is considered to be safe in food industry due to its sensitivity to ultraviolet light and acidic pH [22].…”
Section: Resultsmentioning
confidence: 99%
“…There were other studies for determination of these preservatives individually by chromatographic methods [14]. Some articles reported gradient elution for separation of these at the same time [23, 24].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the analysis of natamycin content for the yoghurts and cheeses samples are illustrated in Figure 3. In the same study natamycin was determined in Turkish yoghurt and natamycin was detected in all yoghurt samples and it is not acceptable according to Turkish codex [14]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…natamycin (colourless, tasteless, flavourless and almost insoluble in water) as a preservative to prevent the development of yeast and moulds in yoghurt. Yeasts are commonly used in yoghurt production, but an increase in lactic acid bacteria induces pH reduction, thereby contributing to an increase in the count and development of yeasts that cause the product spoilage 27 . Bilgic Alkaya and Karalomlu (2016) have demonstrated that 28 yoghurts found in Turkish supermarkets contained natamycin, which is unacceptable as per the Turkish food code 27 .…”
Section: Discussionmentioning
confidence: 99%